Medicinal Plants and Natural Products Used in Cataract Management - Tewari, Devesh; Samoilă, Ovidiu; Gocan, Diana; Mocan, Andrei; Moldovan, Cadmiel; Devkota, Hari Prasad; Atanasov, Atanas G.; Zengin, Gokhan; Echeverría, Javier; Vodnar, Dan; Szabo, Bianca; Crişan, Gianina (Frontiers in Pharmacology, 2019)
Cataract is the leading reason of blindness worldwide and is defined by the presence of any lens opacities or loss of transparency. The most common symptoms of cataract are impaired vision, decreased contrast sensitivity, color disturbance and glare. Oxidative stress is among the main mechanisms involved in the development of age-related cataract. Surgery through phacoemulsification and intraocular lens implantation is the most effective method for cataract treatment, however, there are chances of serious complications and irreversible loss of vision associated with the surgery. Natural compounds consisting of antioxidant or anti-inflammatory secondary metabolites can serve as potential leads for anticataract agents. In this review we tried to document medicinal plants and plant-based natural products used for cataract treatment worldwide, which are gathered from available ethnopharmacological/ethnobotanical data. We have extensively explored a number of recognized databases like PubMed, Science Direct, Google Scholar and Scopus by using keywords and phrases such as “cataract”, “blindness,” “traditional medicine,” “ethnopharmacology,” “ethnobotany,” “herbs,” “medicinal plants” or other relevant terms, and summarized the plants/phytoconstituents that are evaluated in different models of cataract and also tabulated 44 plants that are traditionally used in cataract in various folklore medical practices. Moreover, we also categorized the plants according to scientific studies carried out in different cataract models with their mechanisms of action.